Gastric motility disorders in adolescents with gastroesophageal reflux disease and functional dyspepsia - V.L. Kashina-Yarmak; L.V. Kamarchuk; T.M. Kvaratskheliya (Zaslavsky O.Yu., 2019)
Background. Gastric motility disorders in patients with upper gastrointestinal pathology are one of the key factors in the development of diseases as they disturb the well-being of patients and, therefore, require timely diagnosis and correction. The purpose was to establish the features of gastric motility in adolescents with functional dyspepsia and gastroesophageal reflux disease. Materials and methods. A total of 54 adolescents aged 12-18 years were examined, they were diagnosed with gastroesophageal reflux disease (70.4 %) and functional dyspepsia (29.6 %). Gastric emptying was studied by ultrasound examination of the upper gastrointestinal tract. Results. Functional dyspepsia and gastroesophageal reflux disease in adolescents develop against the background of gastric motility disorders, more often in the form of delayed gastric emptying, regardless of the form of the pathological process and the age of patients. In some patients, these disorders are chronic. Acceleration of gastric emptying is noted much less frequently, it is more typical for younger patients infected with Helicobacter pylori. Conclusions. General pathogenetic mechanisms underlie gastric motility disorders in functional dyspepsia and gastroesophageal reflux disease in adolescents. Evaluation and correction of gastric motility disorders are mandatory when monitoring patients with gastroduodenal pathology.